2007
DOI: 10.1128/jcm.00162-07
|View full text |Cite
|
Sign up to set email alerts
|

Host Genetic Resistance to Symptomatic Norovirus (GGII.4) Infections in Denmark

Abstract: A total of 61 individuals involved in five norovirus outbreaks in Denmark were genotyped at nucleotides 428 and 571 of the FUT2 gene, determining secretor status, i.e., the presence of ABH antigens in secretions and on mucosa. A strong correlation (P ‫؍‬ 0.003) was found between the secretor phenotype and symptomatic disease, extending previous knowledge and confirming that nonsense mutations in the FUT2 gene provide protection against symptomatic norovirus (GGII.4) infections.Volunteer studies have shown that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
67
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 20 publications
8
67
1
1
Order By: Relevance
“…That was particularly clear when individuals of the non-A subgroup were considered, which indicated that the A blood group antigen, which can be expressed on the digestive epithelial cells of secretors only, may have been a protective factor in this particular outbreak. Thus, polymorphisms at both the FUT2 and the ABO loci controlled sensitivity to disease in this shellfish-related outbreak, confirming the importance of these polymorphisms in determining the susceptibility to NoV infection previously observed from either volunteer studies or community outbreaks (2,5,17,24,25). In this study, several strains (NoV, AiV, SaV) were detected either in stool samples or in shellfish.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…That was particularly clear when individuals of the non-A subgroup were considered, which indicated that the A blood group antigen, which can be expressed on the digestive epithelial cells of secretors only, may have been a protective factor in this particular outbreak. Thus, polymorphisms at both the FUT2 and the ABO loci controlled sensitivity to disease in this shellfish-related outbreak, confirming the importance of these polymorphisms in determining the susceptibility to NoV infection previously observed from either volunteer studies or community outbreaks (2,5,17,24,25). In this study, several strains (NoV, AiV, SaV) were detected either in stool samples or in shellfish.…”
Section: Discussionsupporting
confidence: 55%
“…Evidence accumulated over the past 6 years indicates that HBGAs serve as ligands for NoV infection (5,6,15,17,18,25,26,39). However some studies showed discrepant results concerning the effect of either the ABO or the secretor phenotype, raising questions about the importance of HBGAs in norovirus infections (10,12,31,32,37).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Individuals who do not encode a functional FUT2 enzyme have a secretor-negative phenotype, do not express ABH HBGAs on mucosal surfaces, and are resistant to NV infection. Outbreak investigations have confirmed the association between HBGA expression and norovirus infection for some GI and GII strains (37,39,43,49,89). It remains likely that enzymes other than FUT2 may function as norovirus susceptibility factors because secretor-negative individuals have low-level norovirus-reactive antibodies (49,52,53) and can become infected after challenge with a GII.2 strain (52); in addition, some norovirus strains bind to FUT2-independent HBGAs in vitro (35,54,79).…”
mentioning
confidence: 99%
“…HBGAs are complex glycans present on many cell types, including red blood cells and vascular endothelial cells, as well as some epithelial cells (intestinal, urogenital, and respiratory). Volunteer studies and outbreak analyses indicate that binding to these carbohydrates is required for infection, with many strains infecting only a subset of the population based on their HBGA expression (15,20,25,27,28,48,49).…”
mentioning
confidence: 99%